Resilience of Mining Stocks: Impact of Gold Price Volatility and Rupiah Exchange Rate on Antam’s Investment Performance - Dewi, Ririn Fitria; Nurdini, Yuni; Gunawan, Didik; Cahyadi, Lukieto (Jurnal Mantik, 2025)
This study investigates the effect of gold price volatility and rupiah exchange rate on the stock performance of Antam Public Limited Company during four periods of global uncertainty, namely the US-China Trade War (2018-2020), COVID-19 Pandemic (2020-2022), Russia-Ukraine Conflict (2022-2023), and Israel-Hamas Conflict (2023-2024). Using the Vector Error Correction Model (VECM), this analysis evaluates the short-term and long-term relationships between these variables based on daily time series data. The results show significant variation in the effects between periods. Gold price volatility has a strong effect on Antam shares during the US-China Trade War (short and long run) and the COVID-19 Pandemic (long run), reflecting gold's role as a safe haven asset. In contrast, the rupiah exchange rate dominated the influence during the Russia-Ukraine Conflict (short and long run), driven by a weakening exchange rate that boosted export earnings. In the Israel-Hamas Conflict, both variables were insignificant, indicating the limited impact of the regional conflict. These findings underscore the dynamics of market responses to global crises, providing new insights into the resilience of mining stocks and strategic implications for investors and policy makers in managing economic risks